2011
DOI: 10.1002/bit.23328
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and application of virus‐based hybrid nanomaterials

Abstract: A virus is a nanoscaled biomolecular substance composed of genes, protecting capsid proteins, and envelopes. The nanoscale dimensions and surface functionalities of virions have been exploited to attract and assemble inorganic and organic materials to produce functional nanomaterials with large surface areas. Genetic modifications of virus capsid proteins lead to the selective deposition and controlled growth of inorganic substances producing organized virus-based hybrid materials. Due to these properties, vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
107
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 152 publications
(165 reference statements)
0
107
0
Order By: Relevance
“…Here, the reduction of the palladium precursor to Pd(0) is attributed to the presence of Cys residues along insulin fibril surfaces, as indicated by Kurouski et al with tip-enhanced Raman spectroscopy (TERS) [35]. A similar phenomenon where palladium precursors self-mineralized on Cys mutant TMV was also reported by several other research groups [22,36]. Very recently, Sobjerg et al also demonstrated the bacterial synthesis of Pd(0) [37].…”
Section: Chemical Composition Of the Pd-insulin Catalystsmentioning
confidence: 55%
“…Here, the reduction of the palladium precursor to Pd(0) is attributed to the presence of Cys residues along insulin fibril surfaces, as indicated by Kurouski et al with tip-enhanced Raman spectroscopy (TERS) [35]. A similar phenomenon where palladium precursors self-mineralized on Cys mutant TMV was also reported by several other research groups [22,36]. Very recently, Sobjerg et al also demonstrated the bacterial synthesis of Pd(0) [37].…”
Section: Chemical Composition Of the Pd-insulin Catalystsmentioning
confidence: 55%
“…6,[37][38] Moreover, many groups have shown that highly ordered protein assemblies with larger dimensions, like viral particles, are ideal functional scaffolds for the synthesis and organization of NP of different sizes and chemical compositions. 39 Measurements of nanoparticle diameter from TEM micrographs (Figure 1b) demonstrated a correlation of a decrease of mean nanoparticle size as the MPS content increased in the reaction solution ( it is possible to obtain stable and soluble gold clusters (1.5 to 5.2 nm) in organic solvents by using 1-dodecanethiol as a capping agent. 40 The same group synthesized water-soluble gold clusters of 1.8-3.9 nm using tiopronin.…”
Section: Synthesis Of Thiol-coated Gold Particles On Vp6 Nanotubes: Tmentioning
confidence: 98%
“…Attention is now turning toward hybrid systems derived from SN and biomacromolecules capable of self-assembly to give nanotubes [176,177], virus-like particles [178], and viruses [179]. Filling the cavities of nanotubes formed upon the self-assembly of peptide molecules possessing specific structure with silver permits us to obtain composites with unique electrical conductance and electromagnetic properties [176,177].…”
Section: Hybrid Systems With An Organic Polymer Matrixmentioning
confidence: 99%